The Cholinergic Drug Pyridostigmine Alleviates Inflammation During LPS-Induced Acute Respiratory Distress Syndrome - Bricher Choque, Pamela Nithzi; Vieira, Rodolfo P.; Ulloa, Luis; Grabulosa, Caren; Irigoyen, Maria Claudia; De Angelis, Katia; Ligeiro De Oliveira, Ana Paula; Tracey, Kevin J.; Pavlov, Valentin A.; Consolim-Colombo, Fernanda Marciano (Frontiers in Pharmacology, 2021)
Acute respiratory distress syndrome (ARDS) is a critical illness complication that is associated with high mortality. ARDS is documented in severe cases of COVID-19. No effective pharmacological treatments for ARDS are currently available. Dysfunctional immune responses and pulmonary and systemic inflammation are characteristic features of ARDS pathogenesis. Recent advances in our understanding of the regulation of inflammation point to an important role of the vagus-nerve-mediated inflammatory reflex and neural cholinergic signaling. We examined whether pharmacological cholinergic activation using a clinically approved (for myasthenia gravis) cholinergic drug, the acetylcholinesterase inhibitor pyridostigmine alters pulmonary and systemic inflammation in mice with lipopolysaccharide (LPS)-induced ARDS. Male C57Bl/6 mice received one intratracheal instillation of LPS or were sham manipulated (control). Both groups were treated with either vehicle or pyridostigmine (1.5 mg/kg twice daily, 3 mg/day) administered by oral gavage starting at 1h post-LPS and euthanized 24h after LPS administration. Other groups were either sham manipulated or received LPS for 3 days and were treated with vehicle or pyridostigmine and euthanized at 72h. Pyridostigmine treatment reduced the increased total number of cells and neutrophils in the bronchoalveolar lavage fluid (BALF) in mice with ARDS at 24 and 72h. Pyridostigmine also reduced the number of macrophages and lymphocytes at 72h. In addition, pyridostigmine suppressed the levels of TNF, IL-1β, IL-6, and IFN-γ in BALF and plasma at 24 and 72h. However, this cholinergic agent did not significantly altered BALF and plasma levels of the anti-inflammatory cytokine IL-10. Neither LPS nor pyridostigmine affected BALF IFN-γ and IL-10 levels at 24h post-LPS. In conclusion, treatments with the cholinergic agent pyridostigmine ameliorate pulmonary and systemic inflammatory responses in mice with endotoxin-induced ARDS. Considering that pyridostigmine is a clinically approved drug, these findings are of substantial interest for implementing pyridostigmine in therapeutic strategies for ARDS.